2021
DOI: 10.1093/bjsopen/zraa024
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of 2 h of normothermic machine perfusion of donor kidneys in the Eurotransplant Senior Program

Abstract: Background The 5-year graft survival rate of donor kidneys transplanted in the Eurotransplant Senior Program (ESP) is only 47 per cent. Normothermic machine perfusion (NMP) may be a new preservation technique that improves graft outcome. This pilot study aimed to assess safety and feasibility of this technique within the ESP. Methods Recipients were eligible for inclusion if they received a donor kidney within the ESP. Donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 28 publications
0
44
0
1
Order By: Relevance
“…The present study is powered to detect a difference in the proportion of patients experiencing immediate function after transplant between the 2 study groups. In our pilot study (POSEIDON study), the proportion of kidney-related immediate function in the NMP group was 70% compared to 40% in the control group [ 21 ]. Based on the results from this pilot study, we require a sample size of 40 patients per group with a 2-sided α of 5% and power (1-β) of 80%.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The present study is powered to detect a difference in the proportion of patients experiencing immediate function after transplant between the 2 study groups. In our pilot study (POSEIDON study), the proportion of kidney-related immediate function in the NMP group was 70% compared to 40% in the control group [ 21 ]. Based on the results from this pilot study, we require a sample size of 40 patients per group with a 2-sided α of 5% and power (1-β) of 80%.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Because of the normothermic nature of the perfusion, failure of the process leads to warm ischemia. During our previous pilot study, no failure occurred [ 21 ]. If a failure would occur, a highly trained transplant surgeon is present at all time during the perfusion to switch to SCS immediately.…”
Section: Ethics and Disseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in the Netherlands reported the effect on recipients over the age of 65 of receiving a kidney from an ECD following 2 h of NMP [100]. The follow up included 11 patients who received a kidney stored by NMP and a historical cohort of 53 patients who received a kidney stored by HMP or SCS.…”
Section: Modifying the Duration Of Nmpmentioning
confidence: 99%
“…Normothermic machine perfusion (NMP) is a promising alternative to HMP for kidney preservation, and the first clinical studies comparing NMP to HMP have already started. 6 NMP offers the unique ability to fully assess kidney function and viability by allowing the restoration of the renal aerobic metabolism, as it most closely resembles the physiological environment of the kidney. 7 This could theoretically result in less ischemia‐reperfusion injury, and therefore a better survival after donation after circulatory death (DCD) and use of expanded criteria donors (ECD).…”
Section: Introductionmentioning
confidence: 99%